ANALISIS KETERAMPILAN DASAR MENGAJAR GURU DALAM PELAKSANAAN PEMBELAJARAN IPS DI SDN 104 PEKANBARU - Ulfatun Nurul; Mahmud Alpusari; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research is about the analisis of teachers to teach basic skills in IPS learning implementation in SDN 104 Pekanbaru aimed to describe of teachers to teach basic skill in IPS learning implementation in SDN 104 Pekanbaru. Method that used in this research is descriptive method. The research subject is teachers social sciences class IV and V SDN 104 Pekanbaru totaling 2 person. The technique of collecting data in this research uses the technique observation and engineering documentation.As for technical analysis of data used technique score 1 for an activity that looks and 0 for an activity that does not appear.The technique of collecting data in this research uses the technique observation and engineering documentation.As for technical analysis of data used technique score 1 for an activity that looks and 0 for an activity that does not appear. Based on the research known ofthe analysis of teachers to teachbasic skillsIV gradeteacherreceives an averagevalue of64andthe results ofthe analysis of teachers to teachbasic skillsV gradeteacherreceives an averagevalue of49,5.That the activity of grade teacher IV in implementing teaching skills of a teaching in the implementation of learning IPSbased on the results of observations I, II, andIIIobtain good category. The activity of grade teacher V in implementing teaching skills of a teaching in the implementation of learning IPSbased on the results of observations I, II, and IIIobtain enough category.Key Word :Teachers Basic Skills